A Comparative Study Of Self-Efficacy Among Government And Private School Teachers In Tenkasi District - Angel, J. Jeba; .Rajee , M; Brindha, T. Jackuline (Journal of Neonatal Surgery, 2025)
Teacher self-efficacy plays a crucial role in determining teaching effectiveness, student engagement, and overall educational outcomes. This study aims to compare the level of self-efficacy among government and private school teachers in Tenkasi District. A total of 197 teachers were selected using convenience sampling, and data were collected through a structured questionnaire. Statistical tools such as KMO and Bartlett’s Test, factor analysis, and Structural Equation Modelling (AMOS) were applied. The findings indicate that dimensions such as classroom management, instructional strategies, student engagement, and institutional support significantly influence teacher self-efficacy. The study also reveals notable differences between government and private school teachers in terms of self-efficacy levels. The research concludes that strengthening institutional support and continuous professional development can enhance teacher self-efficacy across both sectors...